A model of liquidity hoarding and term premia in inter-banks markets - Viral V. Acharya; David Skeie (Federal Reserve Bank of New York, 2011)
Financial crises are associated with reduced volumes and extreme levels of rates for term inter-bank loans, reflected in the one-month and three-month Libor. We explain such stress by modeling leveraged banks' precautionary demand for liquidity. Asset shocks impair a bank's ability to roll over debt because of agency problems associated with high leverage. In turn, banks hoard liquidity and decrease term lending as their rollover risk increases over the term of the loan. High levels of short-term leverage and illiquidity of assets lead to low volumes and high rates for term borrowing. In extremis, inter-bank markets can completely freeze.
Keywords: G21; G01; E43; 330; inter-bank lending; financial crisis; precautionary demand; rollover risk; Libor-OIS spread; Finanzmarktkrise; Geldmarkt; Bankenliquidität; Zinsstruktur; Risiko; LIBOR Market Modell